LTE‐A compliant multi‐band radio and gigabit/s baseband transmission over 50 m of 1 mm core diameter GI‐POF for in‐home networks. Issue 9 (11th April 2016) - Forni, F.; Shi, Y.; van den Boom, H.P.A.; Tangdiongga, E.; Koonen, A.M.J.
Abstract : The transmission of multiple standard‐compliant long‐term evolution advance (LTE‐A) bands together with a 4‐pulse amplitude modulation (PAM) baseband signal over 50‐m‐long 1 mm core diameter polymethyl methacrylate graded‐index plastic optical fibre is demonstrated. Transmission of eight LTE‐A 64‐QAM bands and a 1.2 Gbit/s 4‐PAM baseband signal over the fibre was achieved resulting in an error vector magnitude <8% and pre‐forward error correction (FEC) BER < 10 −3, respectively.